(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article is devoted to the analysis of the grain sub-sector, namely its formation and development. The grain sub-sector is a key component of the agricultural sector of the economy. The paper presents a consistent review of the history of the grain sub-sector and its role in ensuring food security. The impact of modern technologies of grain cultivation and innovations in the field of agronomy on yields is also considered. In addition, the state of the market infrastructure, issues of export potential and international competition are being investigated. Based on statistical data and expert assessments, the article focuses on the problems and challenges facing the grain sub-sector, such as climate change, lack of resources and the need for modernization. The article examines the stages of development of the grain sub-sector in Russia, which is the basis for the country’s agriculture. Grain crops such as wheat, rye and barley play a key role in the food industry and ensuring food security. The article analyzes various stages of the development of the grain industry from the beginning of the 20th century to the present day, including the influence of internal and external factors such as the social division of labor, the development of capitalism and changes in prices for agricultural products. Special attention is paid to periods of significant change, such as famine in the 1920s, recovery after the Great Patriotic War, and modern achievements related to improved agricultural technology and government support. The article highlights the importance of innovation and sustainable resource management for the further development of the grain sub-sector in Russia.